Primary Cutaneous Gamma–Delta T-Cell Lymphoma Presenting With Hemophagocytic Lymphohistiocytosis in a Young Polynesian Male - Saeed Arabi; Victoria Vardell; Timothy Hanley; Scott Florell; Ahmad Halwani; Ming Lim (Case Reports in Hematology)
Primary cutaneous gamma–delta T-cell lymphoma (PCGD-TCL) is a very rare subtype of cutaneous T-cell lymphoma. We report the case of a young Polynesian male who presented with fever and an abdominal wall rash and highlight the workup leading to the diagnosis of PCGD-TCL. As PCGD-TCL is rare and mimics other medical conditions, its diagnosis requires a high index of suspicion and can be challenging. Hemophagocytic lymphohistiocytosis (HLH) occurs with PCGD-TCL and can be a marker of more invasive disease. There are no well-defined treatment guidelines, but the most common treatment approach is anthracycline-based multiagent chemotherapy followed by allogeneic stem cell transplant. Targeted therapies are being increasingly used as well. Prognosis remains poor and 5‐year survival is < 20%, particularly in more invasive disease. We highlight how this patient’s demographic varies from the published literature and discuss some unique particulars of the diagnostic evaluation and treatment, especially in the presence of concurrent HLH.